Effect of a single session of transcranial direct current stimulation combined with virtual reality training on functional mobility in children with cerebral palsy: A randomized, controlled, double-blind trial. - Ferreira, Stefany Belina; Rezende, Fernanda; Dumont, Arislander Jonathan Lopes; Ferreira, Luiz Alfredo Braun; Lazzari, Roberta Delasta; Oliveira, Claudia Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction:Abnormal postural control in children with cerebral palsy (CP) exerts a negative impact on activities of daily living. The Timed UpandGo (TUG) test is a valid, reliable test for the evaluation of functional mobility in children with CP. Objective:The aim of the present study was to determine the effects of a single session of transcranial direct current stimulation (tDCS) over the primary motor cortex combined with mobility training using a virtual reality system on functional mobility in children with CP. Method: The sample was composed of 12 children with CP aged 4 to 12 years, who were randomly allocated to an experimental group (virtual reality training + active tDCS) and control group (virtual reality training + placebo tDCS). Evaluations involved the TUG test performed 20 minutes before the intervention as well as immediately after the intervention. The paired t-test was used for the intra-group comparisons and both the unpaired t-test and Levene’s test were used for the intergroup comparisons, with a p-value < 0.05 indicative of statistical significance. Results: The data were expressed as mean and standard deviation. In the control group, the time needed to complete the TUG was 14.40 ± 5.79 s before the intervention 13.81 ± 5.18 s after the test (p=0.279). In the experimental group, the time needed to complete the TUG went from 15.73 ± 5.77 s before the test to 13.96 ± 5.48 s after the test(p=0.004). However, no statistically significant difference was found in the inter-group analysis (p=0.853). Conclusion: The findings suggest that tDCSfavors an increase in gait velocity in children with cerebral palsy.